SLEEP DEPRIVATION AND TEACHER HEALTH: A STUDY ON QUALITY OF LIFE AT WORK - Corrêa, Anderson Desbessel; de Carvalho , Lucimar M. Fossatti; Simon, Tiago Teixeira (Seven Editora, 2024)
This study investigates the relationship between sleep quality and well-being among public school teachers. Several factors, such as the work environment, stress, and personal conditions, directly affect the health of teachers, with sleep being a central aspect for physical and mental balance. The study reveals that teachers with better sleep quality tend to have a higher perception of quality of life (QoL) and quality of life at work (QWL), while those with poor sleep demonstrate impairments in both aspects. Sleep deprivation affects several aspects of health, increasing vulnerability to diseases, such as mental and cardiovascular disorders, in addition to impairing performance and physical adaptation. The study, conducted in Passo Fundo, Rio Grande do Sul, used logistic regression analysis, showing that stress increases the chances of poor sleep among teachers by 3.32 times. In addition, those who reported good health are more likely to maintain quality sleep. The research reinforces the need for educational policies to reduce teacher stress, promoting the integral health of these professionals who play an essential role in the formation of society. DOI:https://doi.org/10.56238/sevened2024.037-044